Additive Manufacturing of Al2O3‐Based Carriers for Heterogeneous Catalysis. Issue 5 (30th March 2018) - Ludwig, Theresa; von Seckendorff, Jennie; Troll, Carsten; Fischer, Richard; Tonigold, Markus; Rieger, Bernhard; Hinrichsen, Olaf
Abstract: Additive manufacturing techniques are known for their impressive possibilities in shaping complex structures, which would be beneficial in the production of alumina‐based catalyst shaped bodies. 3D printing of dense ceramics, especially Al2 O3, is known for various printing systems. However, only little effort was done to produce pure alumina parts with increased BET surface areas and sufficient mechanical strength to be used as catalyst carriers. The applicability of four different printing techniques is evaluated and discussed to determine possibilities, strategies and limitations of each technique. Abstract : 3D printing of pure Al2 O3 was investigated in order to obtain catalyst carrier shaped bodies to be used in heterogeneous catalysis. Additive manufacturing of highly dense ceramics is widely known, however, the possibilities, strategies and limitations of producing alumina parts with increased BET surfaces and sufficient mechanical strength are discussed here.